2010
DOI: 10.4103/1817-1745.66663
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric anterior skull base tumors: Our experience and review of literature

Abstract: Surgery for skull base lesions has advanced considerably in the past few years. The improvement in surgical results could be attributed to the availability of refined imaging modalities, modern technological advances and multidisciplinary team approach. In this report, we present our personal experience in the surgical management of 45 children with a variety of skull base lesions treated over 10 years. This article includes a retrospective analysis of the surgical approaches used and their results with a revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Other clinical manifestations noted in the literature include recurrent sinus infection, headache, and heaviness of the head. 4,5 Physical exam includes a thorough cranial nerve exam as a well as an endoscopic exam. Hanbali et al 4 found that the most common clinical findings in children with skull base lesions requiring resection included decreased facial sensation, restricted ocular motility, decreased visual acuity, and proptosis.…”
Section: History and Physical Exammentioning
confidence: 99%
See 3 more Smart Citations
“…Other clinical manifestations noted in the literature include recurrent sinus infection, headache, and heaviness of the head. 4,5 Physical exam includes a thorough cranial nerve exam as a well as an endoscopic exam. Hanbali et al 4 found that the most common clinical findings in children with skull base lesions requiring resection included decreased facial sensation, restricted ocular motility, decreased visual acuity, and proptosis.…”
Section: History and Physical Exammentioning
confidence: 99%
“…Chemotherapy has not been useful for solid tumors of the skull base in children, other than for rhabdomyosarcoma. 5 Cranial radiotherapy, be it external beam or brachytherapy, is frequently used as adjuvant therapy in adults with solid tumors of the skull base. However, it has a more limited role in children because of concerns for generalized growth retardation, pituitary insufficiency and its associated hormonal disturbances, and irreversible visual consequences due to proximity of the orbit.…”
Section: Medicalmentioning
confidence: 99%
See 2 more Smart Citations
“…5,18,19,32,41 For properly selected tumors, EES offers several advantages over traditional methods, including the sparing of disfiguring facial incisions and craniotomy. EES allows the surgeons to access the entire ventral skull base, from the crista galli to the upper cervical spine, with minimal postoperative complications.…”
mentioning
confidence: 99%